Postharvest losses and their determinants: A challenge to creating a sustainable cooking banana value chain in Uganda - Kikulwe, Enoch Mutebi; Okurut, S.; Ajambo, S.; Nowakunda, K.; Stoian, D.; Naziri, D. (MDPI, 2018)
Postharvest losses (PHL) result in direct food and income losses to farmers and consumers globally. PHL reduction strategies offer unique opportunities to contribute to sustainable food systems for increased food security and farm incomes for more than 200 million food insecure people in sub-Saharan Africa. Lack of empirical information remains a major challenge to operationalization of PHL reduction strategies in many countries of the region. This paper utilizes cross-sectional data to determine the extent and factors that are influencing postharvest losses in the cooking-banana value chain in Uganda. We find that 14.9% of all the cooking bananas that are produced in Uganda suffer postharvest deterioration along the value chain (7.2% of the bananas deteriorate completely and have no residual value, while 7.7% deteriorate partially and are sold at discounted prices), mostly affecting retailers. At farm level, female headed households experience more losses than those headed by males. Household headship, household size, proportion of land allocated to banana production, and monthly banana production are the principal determinants of PHL at farm level. At retail level, such losses are mainly determined by sex of the vendor and group membership. The findings call for comprehensive and gender-responsive PHL reduction strategies.